Phytoplankton Analysis and Mapping in Tuban Coastal Based on Chlorophyll-A Concentration Value Using Terra Modis Satellite Imagery - Siti Zainab; Novie Handajani; Minarni Nur Trilita; Primasari Cahya Wardhani (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The coast of Tuban is a fairly dynamic area where the lives of fishermen depend on fishing. Ecosystem changes that occur in the coastal area of Tuban greatly affect the fishing effort. The presence of the phytoplankton themselves cannot be sensed directly. However, the green leaf substance present in the bodies of the phytoplankton can be sensed by sensors in the form of the chlorophyll-a content of the water bodies on the coast. In this study, the distribution of chlorophyll-a on the coast will be mapped using Terra Modis satellite imagery and then analyzed by modeling the distribution so that future predictions can be made on handling water quality on the coast of Tuban so that the economy of fishing communities on the coast of Tuban can be improved. The method used for the mapping is Remote Sensing. The result is a liner mathematical model y = 28.012 x, y is Chlorophyll and x reflectance Rrs_488 which is blue with a degree of determination R2 = 0.9535, and the availability of thematic maps of chlorophyll-a content on the coast of Tuban.